Combined Tevatron upper limit on gg -> H -> W+W- and constraints on the Higgs boson mass in fourth-generation fermion models - Aaltonen, T.; Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Adelman, J.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Zucchelli, S.; et al. (Amer Physical Soc, 2010)
We combine results from searches by the CDF and D0 collaborations for a standard model Higgs boson (H) in the process gg -> H -> W+W- in p (p) over bar collisions at the Fermilab Tevatron Collider at root s = 1.96 TeV. With 4.8 fb(-1) of integrated luminosity analyzed at CDF and 5.4 fb(-1) at D0, the 95% confidence level upper limit on sigma(gg -> H) x B(H -> W+W-) is 1.75 pb at m(H) = 120 GeV, 0.38 pb at m(H) = 165 GeV, and 0.83 pb at m(H) = 200 GeV. Assuming the presence of a fourth sequential generation of fermions with large masses, we exclude at the 95% confidence level a standard-model-like Higgs boson with a mass between 131 and 204 GeV.